Investment, Capacity Utilization, and Changes in Input Structure in the Tin Can Industry - Carter, Anne P. (The Review of Economics and Statistics, 1960)
SIX years ago, the author proposed that technological change be taken into account in a dynamic input-output model by making the input coefficients themselves vary with capital expenditures for growth and change-over. The proposal was rooted in the notion that the input structure of an industry at any given time was an output-weighted average of input structures characterizing technologies of different vintages. Investment in new equipment would increase the relative weight of the latest techniques in the industrial average while scrappage would decrease the relative weight of older techniques. If the technologies representing new capacity installed at various times were known, it would be possible to predict changes in the average technique from these and the time pattern of expenditures on equipment. Considerable effort during the past several years has been directed toward evaluating this approach to the explanation of technological change, that is, to seeing to what extent changes in input structure over time could be predicted from technical parameters for best practice technologies and expenditures on equipment over the period.' Direct verification of a dynamic input-output system with changing coefficients was undertaken,2 but was plagued with three major difficulties: (i) we have not had comparable coefficient matrices at two points of time; (2) available estimates of plant and equipment expenditure for individual industries have been crude, at best; and (3) the system as originally stated incorporated the hypothesis about technological change into the Leontief dynamic system, making the interpretation of its outcome await the solution of the same theoretical problems.3 In view of the obstacles to a satisfactory test in the general equilibrium context, it seemed expedient to investigate the specific question of the relation of technical change to investment more directly, and in particular, separately from the question of what determines the rate of investment itself.4 Last year certain cross-sectional material was made available by the Bureau of the Census for a pilot study in the analysis of technological change.5 On the basis of this information, we began to investigate in some detail to what extent it is possible to account for changes in the distribution of input coefficients of individual plants in a given industry in terms of the distribution of their equipment expenditure patterns. Specifically, the present study treats the question: to what extent is it possible to explain changes in the distribution of individual plants' input coefficients in terms of their respective equipment expenditure patterns and a common incremental or best practice production function. The approach will be successful to the extent that the specific characteristics of installed equipment govern quantitative inputoutput relationships and that plants in a given industry tend to purchase the same kinds of equipment at the same time. General experience tells us that neither of these conditions prevails entirely, in any industry. During the same period, some plants will be buying new process equipment and other plants new materials-handling equipment. Older plants will be limited in their alterations, while newer plants will be able to take advantage of a wider range of alternatives. Initial differences in technology, related to product quality or location, may be expected to govern additions to, or replacements of, capacity as well.